Local Belief and the Negotiation of EFL Teachers’ Identity in an Asian Country - Sipe, Marlon; Avila, Christine Faith (Journal of Education Culture and Society, 2024)
Aim. This study investigates the local belief and the negotiation of English as a Foreign Language (EFL) teachers' identity within the Asian context.Methods. Framed within the Martha Pennington (2014) model, this qualitative research examines the complex interplay between local beliefs and the participants’ identity formation through in-depth interviews. The data was collected from three (3) EFL teachers operating at local Asian schools.Results. The findings reveal the significance of local beliefs in shaping teachers' instructional practices, classroom interactions, and professional identities. This research sheds light on the dynamic nature of EFL pedagogy in culturally diverse settings as it underscores the dialectical process through which EFL teachers negotiate their identities within the local cultural and educational milieu.Conclusions. It can be concluded that this research contributes to the field of EFL education by highlighting the need for teacher training programmes that address the diverse cultural and contextual factors that influence the formation of EFL teachers' identities.